Priorities for developing a modelling and scenario analysis framework for waterborne pathogen concentrations in rivers worldwide and consequent burden of disease - Hofstra, N.; Vermeulen, L.C.; Derx, J.; Florke, M.; Mateo-Sagasta, Javier; Rose, J.; Medema, G. (Elsevier, 2019)
Diarrhoea caused by waterborne pathogens still has a large burden of disease. We introduce a modelling and scenario analysis framework that enables better understanding of sources of and possible future changes in the disease burden due to environmental change and management implementation. The state-of-the-art research that can contribute to the development of the framework at the large scale is analysed, together with research gaps and opportunities for future research. Priorities have been identified and these include implementation of Quantitative Microbial Risk Assessment and application of the models in scenario analyses. The credibility of the model outputs should be central in the analysis, for example by developing stochastic models. Implementation of the framework contributes towards achieving the Sustainable Development Goals.